Transculturation : cities, spaces and architectures in Latin America - Hernández, Felipe, 1971-; Millington, Mark; Borden, Iain (Critical studies (Amsterdam, Netherlands), 2005)
Transculturation: Cities, Spaces and Architectures in Latin America explores thecritical potential inherent in the notion of "transculturation" in order to understand contemporary architectural practices and their cultural realities in Latin America. Despite its enormous theoretical potential and its importance within Latin American cultural theory, the term transculturation had never permeated into architectural debates. In fact, none of the main architectural theories produced in and about Latin America during the second half of the twentieth century engaged seriously with this notion as a w.